Pharmacokinetics of a Single Dose of Turmeric Curcuminoids Depends on Formulation: Results of a Human Crossover Study. Issue 7 (20th April 2021) - Fança-Berthon, Pascale; Tenon, Mathieu; Bouter-Banon, Sabrina Le; Manfré, Alexis; Maudet, Corinne; Dion, Angelina; Chevallier, Hélène; Laval, Julie; van Breemen, Richard B
ABSTRACT: Background: Curcuminoids from turmeric rhizome have significant health benefits but low bioavailability. Objectives: To assess the pharmacokinetics of a novel natural turmeric dried colloidal suspension compared with 4 other turmeric formulations (including a standardized extract) at their respective recommended dosages. Methods: Thirty healthy men and women (18 to 45 y old) were enrolled in a randomized, open-labeled, crossover trial, and sequentially consumed single oral doses of standard turmeric extract (1500 mg), liquid micellar preparation (1000 mg), piperine-curcuminoid combination (1515 mg), phytosome formulation (1000 mg), or the dried colloidal suspension (300 mg). Eleven blood samples were obtained over 24 h, plasma was extracted with or without deconjugation with β-glucuronidase or sulfatase, and ultra-high-pressure liquid chromatography/tandem MS was used to quantify the 3 parent curcuminoids and 12 metabolites. Classical pharmacokinetics parameters were derived. Results: The total AUC values of unconjugated curcuminoids were highly variable within participants, with no significant differences between formulations. However, the AUC values for total curcuminoids (including all metabolites) showed significant product effects. Indeed, the micellar preparation delivered higher levels of total curcuminoids than any other formulation (8540 ng·h/mL), reaching significance when compared with the dried colloidal suspension and standard extract (6520 and 5080 ng·h/mL, respectively). After dose normalization, both micellar and dried colloidal formulations showed significantly higher AUC levels than the standard extract (respectively 136 and 72.9, compared with 3.7 ng·h/mL/mg). Total curcuminoid absorption levels were also significantly higher for the dried colloidal suspension when compared with either piperine or phytosome formulations. Interestingly, no significant differences were observed between the piperine-curcuminoid combination and the standard extract. No serious adverse events were reported. Conclusions: The administration of a low dose of the novel natural dried colloidal suspension provided high unconjugated and conjugated curcuminoid absorption, with significant beneficial differences when compared with the high dose of standard extract. This trial was registered at clinicaltrials.gov as NCT03621865.